Salt management: a key to irrigation sustainability in arid climates - Oster, J. D., author; Kaffka, S. R., author; Wichelns, D., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Salt management is a critical component of irrigated agriculture in arid regions. Successful crop production cannot be sustained without maintaining an acceptable level of salinity in the root zone. This requires drainage and a location to dispose drainage water, particularly, the salts it contains, which degrade the quality of receiving water bodies. Despite the need to generate drainage water to sustain productivity, many irrigation schemes have been designed and constructed with insufficient attention to drainage, to appropriate re-use or disposal of saline drainage water, and to salt disposal in general. To control the negative effects of drainage water disposal, state and federal agencies in several countries now are placing regulations on the discharge of saline drainage water into rivers. As a result, many farmers have implemented irrigation and crop management practices that reduce drainage volumes. Farmers and technical specialists also are examining water treatment schemes to remove salt or dispose of saline drainage water in evaporation basins or in underlying groundwater. We propose that the responsibility for salt management be combined with the irrigation rights of farmers. This approach will focus farmers' attention on salt management and motivate water delivery agencies and farmers to seek efficient methods for reducing the amount of salt needing disposal and to determine methods of disposing salt in ways that are environmentally acceptable.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.
Keywords: drainage; economics; policy; salinity; salt loads